International migration and remittances: A review of economic impacts, issues and challenges from the sending country’s perspective - Tullao, Tereso S., Jr. (Animo Repository, 2016)
The paper reviews the motivations of people to migrate and remit as well as the impacts of migration and the effects of remittances. Reasons for migration are quite varied ranging from economic asymmetries (also known as push-pull factors), demographic asymmetries, investment in human capital, maximization of household income, the culture of migration, and the movement in natural persons. On the other hand, remittances are sent to the home country for altruistic, exchange, strategic and insurance motives as well as an arbitrage in interspatial differences in purchasing power. The impacts of migration and remittances are felt on both the household and national levels of the sending country including various dimensions of the macro-economy. International migration and its accompanying remittances are realities that have to be accepted given the positive contributions and the negative consequences attached to it. Thus, there is a need to mitigate its social costs while enhancing its positive contributions to the individuals, households, community and society. It has been observed that there are positive effects on the family as well as psychological cost. These dual effects are likewise felt by the community and the national economy. Accepting the costs and recognizing the benefits is crucial in managing the phenomenon of international migration as a relevant social reality.